Traditional worldview and religious ideology in the turkic khanates (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the history of the Turkic states, which arose in Central Asia in the 7th century, the definition and assessment of the essence of religious ideology in these states remains unresolved due to the lack of documentary data. Determining the influence of the religious factor on the fact that the Turks, who united different nomadic tribes with a common ethnic origin, economic and economic type and built their own state, in a relatively short time again disintegrated and disappeared, despite the favorable political situation at that time, is still unclear .Researchers associate the political crisis of the nomadic state mainly with the deterioration of the state of the medieval Turkic states: internal political disagreements, the collapse of economic and economic traditions, and attempts by neighboring countries to create internal conflicts. However, some researchers believe that the destruction of the states built by the Turks and their transformation into a new form was caused by spiritual processes in these states. The purpose of the article is to reveal the religious aspects of the causes and therefore it is devoted to the study of spiritual changes and features of the growth of the traditional worldview that supported the religious ideology of the Turks during the founding and fall of the First Turkic Khaganate.
Keywords: Turkic Kaganate, traditional worldview, world religions, religious-ideological struggle, statehood, continuity of tradition